2012
DOI: 10.1063/1.3687147
|View full text |Cite
|
Sign up to set email alerts
|

Metallic state induced in Eu2Ru2O7 by hole creation and orbital overlap in the t2g bands

Abstract: Articles you may be interested inEnhanced ferromagnetism, metal-insulator transition, and large magnetoresistance in La1−xCaxMn1−xRuxO3 free of eg -orbital double-exchange Magnetic and transport properties of ( La 0.7−2x Eu x )( Ca 0.3 Sr x ) MnO 3 : Effect of simultaneous size disorder and carrier density J. Appl. Phys. 95, 4934 (2004); 10.1063/1.1667258 Effect of Li doping on the magnetotransport properties of La 0.7 Ca 0.3−y Li y MnO 3 system: Decrease of metal-insulator transition temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Pb 2 Ru 2 O 6.5 , Tl 2 Ru 2 O 7−y ), as these contain either A-site ions of different formal charge in the case of Pb 2+ , or have [49]. Values of electrical resistivity were taken from references [1,3,22,26,50,51,52,53]. contributions from overlap between empty 6s states and filled states, as in the case of Tl 3+ .…”
Section: Electrical Transport In Ru Pyrochloresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pb 2 Ru 2 O 6.5 , Tl 2 Ru 2 O 7−y ), as these contain either A-site ions of different formal charge in the case of Pb 2+ , or have [49]. Values of electrical resistivity were taken from references [1,3,22,26,50,51,52,53]. contributions from overlap between empty 6s states and filled states, as in the case of Tl 3+ .…”
Section: Electrical Transport In Ru Pyrochloresmentioning
confidence: 99%
“…Even an isovalent substitution of Ln 3+ by Bi 3+ may not allow straightforward comparison; structural studies of Bi 2 Ru 2 O 7 have shown that Bi 3+ atoms are off-centred due [50]. Values of electrical resistivity were taken from [1,3,20,26,[51][52][53][54].…”
Section: Electrical Transport In Ru Pyrochloresmentioning
confidence: 99%
“…Our transport data obtained in the intermediate and high field regimes follow a Mott Variable Range Hopping (VRH) or Efros-Shklovskii mechanism. 32 Since the e' g 3 electrons are highly localized, a soft Coulomb gap Δ c of around ~ 0.29 eV can be interpreted as an increase in the density of states close to and above the E F due to the excited states from the extrinsic Eu 3+ .…”
Section: B Molecular Orbital Energy Diagrammentioning
confidence: 99%
“…In Eu 2-x Ca x Ru 2 O 7 and Eu 2 Ru 2-x Re x O 7 a delicate balance between the localized and delocalized states evolves towards a metal-like behaviour. 9,32 On the other hand, Tl 2 Mn 2 O 7 and Tl 2 Ru 2 O 7 show colossal magnetoresistance and spin gap formation, respectively. 26,33…”
Section: B Molecular Orbital Energy Diagrammentioning
confidence: 99%
See 1 more Smart Citation